STUDI LITERATUR FAKTOR KEBIJAKAN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA PEKERJA PROYEK KONSTRUKSI - Handayani, Febry; Lendra, Lendra; Happy Puspasari, Veronika (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2024)
Examining the effect of the “occupational safety and health (K3) policy on worker performance” is very useful in order to get the influence of OSH involvement when it impacts workers. In construction projects, there are many elements that influence the success of the project, one of which is the quality of worker performance. Aims to find OSH policy factors and OSH policy factors during a pandemic on the performance of construction project workers by carrying out a literature study on several previous studies. The research methodology is conducting a literature search using the Publish or Perish application. Relevant literature is then used as a source of research. The results of the literature study, there are 39 OHS policy factors that are considered to have the potential to affect worker performance consisting of 30 OHS policy factors and 9 OHS policy factors during the pandemic on worker performance. There are 7 factors that are the most common in previous research, namely: the company provides work safety equipment, workers often use personal protective equipment to prevent incidents while carrying out their work. The implementation of the K3 system in order to guarantee the situation “The health of the workers, as well as providing a comfortable environment when they arrive has a good impact on the continuity of the workers in the Company”. Through the implementation of this facilitated programming implementation, the Company can improve the quality of workers and be able to manage their time properly when completing their work.